Evaluación y reflexiones de la inclusión financiera en el perú, a través del mapa estrategico de heimann - Villamonte Blas, Ricardo (2013)
Financial participation is one of the main components that explain poverty. Heimann Strategic Map allows a first crosscutting assessment of this problem. In Peru there is a financial system which is very solid, well supervised, capitalized, and liquid, but a systematic plan is required to allow gradually reduce financial exclusion, since interventions carried out by different involved financial institutions are due to institutional views. These do not meet real demand requirements and are not organized. In addition to this, in order to make the plan sustainable, it is necessary to incorporate strategies and activities both from supply and demand. Peru has different institutions with certain experience and willingness and it is required an call and an action plan led by the Government.